2016
DOI: 10.1016/j.ajog.2015.09.086
|View full text |Cite
|
Sign up to set email alerts
|

Association of cervical precancer with human papillomavirus types other than 16 among HIV co-infected women

Abstract: Background HIV-seropositive women face high risk for infection with oncogenic human papillomavirus (oncHPV) types, abnormal Pap test results, and precancer, but cervical cancer risk is only modestly increased. Human papillomavirus (HPV)16 is highly oncogenic but only weakly associated with HIV status and immunosuppression, suggesting HPV16 may have a greater innate ability to evade host immune surveillance than other oncHPV types, which in turn should result in a greater relative increase in the prevalence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
41
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 19 publications
7
41
1
Order By: Relevance
“…It has been hypothesized that HPV16 is more capable of evading host‐immune control than other carcinogenic types. In patients who have impaired immune function, other genotypes may persist longer and cause precancers or cancers more often compared with immune‐competent individuals . This could explain the lower relative proportion of HPV16‐positive cancers among HIV‐positive versus HIV‐negative men and women (Fig.…”
Section: Strategies For Anal Cancer Screening and Early Detectionmentioning
confidence: 99%
“…It has been hypothesized that HPV16 is more capable of evading host‐immune control than other carcinogenic types. In patients who have impaired immune function, other genotypes may persist longer and cause precancers or cancers more often compared with immune‐competent individuals . This could explain the lower relative proportion of HPV16‐positive cancers among HIV‐positive versus HIV‐negative men and women (Fig.…”
Section: Strategies For Anal Cancer Screening and Early Detectionmentioning
confidence: 99%
“…HPV-16 had the highest prevalence in the study population (regardless of HIV status) ( Figure 1 immunocompetent ones) [19]. By contrast, studies in countries with heterogeneous populations have indicated that HPV-16 continues to have the highest prevalence (regardless of HIV status) and contributes towards development of cervical lesions in the population living with HIV [2,20,21].…”
Section: Discussionmentioning
confidence: 91%
“…The clinical characteristics (determined exclusively in HIV-positive women) showed that a viral load >100 000 copies/ml (adjusted OR 7.76; 95% CI 1.64-63. 19) was strongly associated with multiple infection; by contrast, women with CD4 cell counts >500 cells/mm 3 were at lower risk of multiple infection (adjusted OR 0.38; 95% CI 0.13-0.98) ( Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the prevalence of HPV16, which causes approximately 55–60% of all cervical cancers in the general population, was found to be the least affected by HIV status and CD4 count of any oncogenic HPV, based on prevalence ratios (PR) in multiplicative multivariate models . This relative independence from host immune status has been interpreted as evidence that HPV16 may have an innate ability to avoid the effects of immunosurveillance, which could partly explain the high prevalence of HPV16 in the general population and its unique carcinogenicity …”
Section: Introductionmentioning
confidence: 99%